Internet and Consumer behaviour in Travel and Tourism: A European Cross-National Analysis - Navío-Marco, Julio; Ruiz-Gómez, Luis Manuel; Sevilla-Sevilla, Claudia (Journal of Reviews on Global Economics, 2018)
The emergence of the internet and the development of ICTs have transformed communications and the marketing of products and services. This paper examines the extent to which the internet has penetrated homes in the various EU countries and how online consumers behave in activities linked to travel and tourism. The years 2007 and 2016 were analysed in order to make a comparison over time of the progression of the internet and ICTs among EU citizens and to examine similarities and differences in behaviour patterns in the field of tourism. This study helps confirm a correlation between digitalisation and ICTs in buying habits for tourism products and services, finding that though digital divides between countries are narrowing over time, this is not the case in the use of ICTs in tourism in particular. Our findings indicate divergent behaviour patterns and trends in online travel and accommodation management and in the way that ICTs are used in the European Union.